Sixteenth‐century German woodcut of a male infant with possible disorganization. Issue 2 (14th August 2015) - Heyne, T.F.; Robin, N.H.; Lin, A.E.
Abstract : History has preserved a beautiful 16th century woodcut print, which depicts an infant with several malformations. The German inscription describes the infant's hypotonia and ectopic growths, and the image itself shows a child with an ectopic accessory third lower limb, a large papilla, and an omphalocele‐like growth. The 'case' bears striking similarity to reported human cases of the disorganization (Ds) syndrome. This article describes the woodcut, describes Ds, and then explains how the image may represent the earliest depiction of Ds in history. Abstract : Section Editor: Albert E. Chudley, email:Chudley@cc.umanitoba.ca